Respiratory virus surveillance in hospitalised pneumonia patients on the Thailand-Myanmar border. - Turner, P; Turner, C; Watthanaworawit, W; Carrara, V; Cicelia, N; Deglise, C; Phares, C; Ortega, L; Nosten, F (BioMed Central, 2013)
BACKGROUND: Pneumonia is a significant cause of morbidity and mortality in the developing world. Viruses contribute significantly to pneumonia burden, although data for low-income and tropical countries are scarce. The aim of this laboratory-enhanced, hospital-based surveillance was to characterise the epidemiology of respiratory virus infections among refugees living on the Thailand-Myanmar border. METHODS: Maela camp provides shelter for ~45,000 refugees. Inside the camp, a humanitarian organisation provides free hospital care in a 158-bed inpatient department (IPD). Between 1st April 2009 and 30th September 2011, all patients admitted to the IPD with a clinical diagnosis of pneumonia were invited to participate. Clinical symptoms and signs were recorded and a nasopharyngeal aspirate (NPA) collected. NPAs were tested for adenoviruses, human metapneumovirus (hMPV), influenza A and B, and RSV by PCR. RESULTS: Seven hundred eight patient episodes (698 patients) diagnosed as pneumonia during the enhanced surveillance period were included in this analysis. The median patient age was 1 year (range: < 1-70), and 90.4% were aged < 5 years. At least one virus was detected in 53.7% (380/708) of episodes. Virus detection was more common in children aged < 5 years old (<1 year: OR 2.0, 95% CI 1.2-3.4, p = 0.01; 1-4 years: OR 1.4, 95% CI 0.8-2.3, p = 0.2). RSV was detected in 176/708 (24.9%); an adenovirus in 133/708 (18.8%); an influenza virus in 68/708 (9.6%); and hMPV in 33/708 (4.7%). Twenty-eight episodes of multiple viral infections were identified, most commonly adenovirus plus another virus. RSV was more likely to be detected in children <5 years (OR 12.3, 95% CI 3.0-50.8, p = 0.001) and influenza viruses in patients ≥5 years (OR 2.8, 95% CI 1.5-5.4, p = 0.002). IPD treatment was documented in 702/708 cases; all but one patient received antimicrobials, most commonly a beta-lactam (amoxicillin/ampicillin +/-gentamicin in 664/701, 94.7%). CONCLUSIONS: Viral nucleic acid was identified in the nasopharynx in half the patients admitted with clinically diagnosed pneumonia. Development of immunisations targeting common respiratory viruses is likely to reduce the incidence of pneumonia in children living refugee camps and similar settings.